Circulating PUFAs and their associations with abdominal obesity and hyperglycaemia among vegetarians and non-vegetarians: Insights for personalised nutrition from a cross-sectional study - Yuan Kei Ching; Yit Siew Chin; Mahenderan Appukutty; Yoke Mun Chan (PLoS ONE, 2026)
This study explores the associations between circulating polyunsaturated fatty acids (PUFAs), abdominal obesity and hyperglycaemia among vegetarians and non-vegetarians with distinct dietary PUFA intakes, as limited evidence exists on how circulating PUFA concentrations differ between these dietary groups and relate to metabolic risks. In this cross-sectional study, serum PUFA profiles and their associations with abdominal obesity and hyperglycaemia were examined . A total of 127 vegetarians and 132 non-vegetarians from Malaysia participated in the present study. Vegetarians had higher circulating concentrations of linoleic acid (LA), alpha-linolenic acid (ALA), and the n- 6: n- 3 PUFA ratio. They had lower concentrations of eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA), and docosahexaenoic acid (DHA) than non-vegetarians. Among vegetarians, higher circulating arachidonic acid (ARA) concentrations were associated with an increased risk of hyperglycaemia (odds ratio [OR]: 1.06, 95% confidence interval [CI]: 1.00–1.11). In non-vegetarians, higher circulating ARA was associated with a higher risk of abdominal obesity (OR: 1.05, 95% CI: 1.00–1.09), while lower circulating DHA was associated with a reduced odds of abdominal obesity (OR: 0.95, 95% CI: 0.90–0.99). Conversely, a high circulating n- 6: n- 3 PUFA ratio was associated with a lower risk of hyperglycaemia (OR: 0.96, 95% CI: 0.93 - 1.00) among non-vegetarians. These findings highlight distinct metabolic responses to PUFA profiles between vegetarians and non-vegetarians, suggesting the need for tailored dietary strategies to address abdominal obesity and hyperglycaemia for both groups.